Facial Spinulate Demodicosis - Zahr Allayali A (Dove Medical Press, 2021)
Ahmed Zahr Allayali Department of Internal Medicine, Umm Al-Qura University, Makkah, Saudi ArabiaCorrespondence: Ahmed Zahr AllayaliDepartment of Internal Medicine, Umm Al-Qura University, Makkah, Saudi ArabiaTel +966530041029Email ahmedz98@hotmail.comAbstract: Hyperkeratotic spicules are rare cutaneous lesions associated with underlying systemic illnesses. In more recent times, facial spinulate demodicosis has been suggested as an etiological factor. Demodicosis is a common dermatological condition characterized by the presence of Demodex mites in the pilocutaneous follicles. This report describes the case of a 40-year-old otherwise healthy woman who reported having undetected facial follicular spicules as a result of demodicosis. The diagnosis was confirmed by physical examination and skin punch biopsy. Initial treatment with 5% permethrin did not resolve the rash. As such, 1% Ivermectin was prescribed, after which the rash resolved completely within 3 weeks.Keywords: spinulate, Demodex folliculorum, demodicosis